Staging to join non‐kin groups in a classical cooperative breeder, the Florida scrub‐jay. Issue 5 (28th February 2022) - Suh, Young Ha; Bowman, Reed; Fitzpatrick, John W.
Abstract: Why unrelated members form groups in animal societies remains a pertinent topic in evolutionary biology because benefits for group members often are not obvious. We studied subordinates that disperse to join unrelated social groups in the Florida scrub‐jay Aphelocoma coerulescens, a cooperative breeding species mainly composed of kin‐based groups. We evaluated potential adaptive benefits of dispersing to become an unrelated helper (staging) versus remaining home and dispersing only to pair and breed (direct dispersal) to understand why non‐kin‐based groups form. Using 35 years of demographic data, we quantified life‐history aspects of staging individuals and tested associations between social and ecological factors on the natal and staging territories. We compared fitness outcomes between dispersal strategies by analysing survival, breeding recruitment and direct reproductive output. We tested for sexual asymmetry potentially driven by differences in territory acquisition patterns and female‐biased dispersal for this species. Of birds that reached 1 year, 28% staged at a non‐natal territory before breeding or disappearing. Staging dispersers departed at younger ages and moved greater distances than direct dispersers. When looking at proximate factors on the natal territory associated with staging, males left groups with many same‐sex helpers, while females often left when their father disappeared. For both sexes, staging individuals more likely came from high‐quality territories and joined groups with fewer same‐sex helpers than in their natal group. While staging and direct dispersers did not differ in survival or likelihood of becoming a breeder, staging males became breeders later and had lower lifetime reproductive success than direct dispersers. In Florida scrub‐jays, staging appears to be an alternative strategy for female helpers, but a best‐of‐a‐bad‐situation for males. This sexual asymmetry is consistent with males having more options than females to achieve higher reproductive success by breeding near home. Trade‐offs in cost–benefits of departing the natal territory and joining unrelated groups as a helper seem to best explain alternative dispersal patterns, with optimal social queues primarily driving the benefits. This research highlights plasticity in dispersal behaviour in response to social and environmental conditions and offers a new perspective in our understanding of non‐kin‐based social groups. Abstract : Using comprehensive analyses on long‐term data and lifetime reproduction, this study provides insights into why non‐kin‐based groups form, especially when kin‐based groups are the norm for a species. The results indicate that social queues on the natal territory and comparable lifetime reproductive success likely promote staging, a previously overlooked behaviour in Florida scrub‐jays.